492. Long-Term Outcomes of Clostridium difficile Infection Among Medicare Beneficiaries. (26th November 2018) - Hatfield, Kelly M; Baggs, James; Winston, Lisa G; Parker, Erin; Martin, Brittany; Meek, James I; Olson, Danyel; Farley, Monica M; Revis, Andrew; Holzbauer, Stacy; Bye, Maria; Wilson, Lucy; et al.
Abstract: Background: Clostridium difficile infection (CDI) is a common healthcare-associated infection, particularly among older adults. We used laboratory-confirmed CDI surveillance data from 8 states participating in the Centers for Disease Control and Prevention's Emerging Infections Program linked to claims data for Centers for Medicare and Medicaid Services (CMS) beneficiaries to measure variation in 1-year outcomes associated with CDI. Methods: A CDI case was defined as a positive C. difficile stool test in 2014 in a person without a positive test in the prior 8 weeks. Cases aged ≥65 years were linked to their CMS beneficiary ID using unique combinations of date of birth, sex, and zip code. Each case was matched to five control beneficiaries who did not link to any case and were residents of the same catchment area. Inclusion criteria were continuous fee-for-service Medicare for the entire study period (1 year before and after event date), and no hospitalization or skilled nursing facility stay with an ICD-9-CM code for CDI in the year prior to their match date. Multivariable logistic regression models were used to compare mortality and hospitalization for 1 year following the event date between beneficiaries with and without CDI, adjusting for age, sex, race, catchment area, chronic conditions, number of hospitalizations in the prior year, and hospitalization status at the time of and 7 days preceding the event date. Results: Of 5, 097 cases aged ≥65, 3, 082 (60%) were linked to a CMS ID, and 1, 832 (59%) met inclusion criteria. In crude analysis, 34% of beneficiaries with CDI died within 1 year, compared with 5% of beneficiaries without CDI. Beneficiaries with CDI were also more likely to be hospitalized in the subsequent year (54% vs. 17%). Beneficiaries with CDI had a higher adjusted odds of death (adjusted OR 3.01, 95% CI: 2.46, 3.69) and hospitalization within 1 year (adjusted OR 1.93, 95% CI: 1.65, 2.25) than those without CDI. Conclusion: Older adults with CDI were three times more likely to die in the year following infection and nearly two times more likely to be hospitalized compared with those without CDI, revealing independent long-term risk of poor outcomes. This excess morbidity and mortality supports the need to develop novel CDI prevention strategies for this population. Disclosures: All authors: No reported disclosures.